Closely related yet different: a borylene and its dimer are non-interconvertible but connected through reactivity. Issue 8 (29th January 2018) - Auerhammer, Dominic; Arrowsmith, Merle; Dewhurst, Rian D.; Kupfer, Thomas; Böhnke, Julian; Braunschweig, Holger
Abstract : This side-by-side reactivity study of a borylene and a diborene with the same empirical formula demonstrates their non-interconvertibility. Abstract : The self-stabilizing, tetrameric cyanoborylene [(cAAC)B(CN)]4 (I, cAAC = 1-(2, 6-diisopropylphenyl)-3, 3, 5, 5-tetramethylpyrrolidin-2-ylidene) and its diborene relative, [(cAAC)(CN)BB(CN)(cAAC)] (II ), both react with disulfides and diselenides to yield the corresponding cAAC-supported cyanoboron bis(chalcogenides). Furthermore, reactions ofI orII with elemental sulfur and selenium in various stoichiometries provided access to a variety of cAAC-stabilized cyanoboron–chalcogen heterocycles, including a unique dithiaborirane, a diboraselenirane, 1, 3-dichalcogena-2, 4-diboretanes, 1, 3, 4-trichalcogena-2, 5-diborolanes and a rare six-membered 1, 2, 4, 5-tetrathia-3, 6-diborinane. Stepwise addition reactions and solution stability studies provided insights into the mechanism of these reactions and the subtle differences in reactivity observed betweenI andII .